Alternation some sounds in Turkic languages (Eurasian Journal of Philology Science and Education, 2015)
Language, as a natural phenomenon, is being developed all the time and is considered as the whole unity of language elements, formed as a result of its realization as a means of communication. So as a consequence there are different changes in the language and different phenomena appear as a rule, including sound alternation. So in thestructure of morphemes and on their combination different sound changes can take place and they can’t be explained in terms of phonetic regularities. Such phenomena must be considered in terms of phonology and morphonology. One of such sound alternation in Kazakh language is the sound accordance. Alternation, which means sound accordance in Kazakh language, is being considered in this article in terms ofmorphonology. Besides this, the article analyses differences of phonetical sound alternation with its morphonology alternation.Is morphonological phenomena as a consequence of alternation of vowel and consonant sounds in Kazakh language,as well as positional and non-positional morphonological sound alternations.
Keywords: morphonological phenomenon; some consonants; alternation; phonetic patterns